Pengaruh Edukasi Terhadap Tingkat Kepatuhan Minum Obat Dan Prilaku Diet Pada Pasien Diabetes Mellitus Tipe II di RSUD Kabupaten Bintan - Faria Handayani; Fitriany Suangga; Ennimay Ennimay (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Diabetes is a chronic disease in the form of a metabolic disorder characterized by blood sugar levels that exceed normal limits and one of them is Diabetes Mellitus Type II. Effective education to improve self-management in Type II Diabetes Mellitus sufferers. Non-compliance with Diabetes Mellitus treatment is currently still a quite important problem in the management of Diabetes Mellitus patients. To find out and analyze the effect of education on the level of compliance with medication and diet in Type II Diabetes Mellitus Patients at the Bintan Regency Regional Hospital. The research used Pre-experimental, with a One Group Pretest Posttest research design by analyzing the effect of providing education on the level of compliance with taking medication and diet in Type II Diabetes Mellitus Patients at the Bintan Regency Hospital. The results of the analysis of the Wilcoxon signed ranks test, the level of compliance with taking medication and dietary behavior after being given education was better than before being given education with a significance value of P < 0.0001, less than 0.05, meaning that there was a significant influence before and after being given education on the level of compliance. taking medicine and diet. For future researchers, the problem of patient education should be deepened so that patients understand more about the disease they are suffering from.